Nucleotide sequence homology between the immunoglobulin A1 protease genes of Neisseria gonorrhoeae, Neisseria meningitidis, and Haemophilus influenzae. - Koomey, J M (1984)
Isolated DNA fragments encoding the immunoglobulin A1 (IgA1) protease of Neisseria gonorrhoeae were used as hybridization probes to search for homologous sequences in whole cell DNA from Neisseria meningitidis and Haemophilus influenzae. Significant homology was detected. That the detected homology represented IgA1 protease-specific sequences was confirmed by the cloning of these sequences in Escherichia coli HB101 and demonstrating the expression of IgA1 protease by these transformed cells. Molecular probing of commensal Neisseria and Haemophilus species, which do not elaborate IgA1 protease activity, revealed that they were devoid of sequence homology with the cloned IgA1 protease gene DNA.